2018
DOI: 10.7150/thno.22565
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-Derived Exosomal MiR-27a Induces Insulin Resistance in Skeletal Muscle Through Repression of PPARγ

Abstract: The mechanism by which adipocyte-derived endocrine factors promote insulin resistance in skeletal muscle are not fully understood. MiR-27a is highly expressed in sera of obese individuals with prediabetes and T2DM, and mainly derived by adipose tissues. Thus, miR-27a secreted into circulation by adipose tissue may regulate insulin resistance in skeletal muscle.Methods: The association between miR-27a and insulin resistance in skeletal muscle was determined in obese children, high-fat diet-induced miR-27a knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
187
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(193 citation statements)
references
References 43 publications
3
187
2
1
Order By: Relevance
“…Exosomes are extracellular microvesicles (30 to 150 nm in diameter) derived from various cells, transferring different proteins, non-coding RNA and coding RNA, which have been looked as diseases biomarkers or cellcell communication factors [31,32]. Increasing studies have unveiled that exosomes derived from the insulinresistant adipocyte were implicated in the skeletal muscle insulin resistance, obesity-related liver disease, atherosclerosis, and lung cancer [33][34][35][36]. Given the broad spectrum of the discoveries of the function of these exosomes, it is not surprising that exosomes derived from insulin-resistant adipocytes, functioned as independent metabolic units, which might provide a promising therapeutic target on the insulin resistance, diabetes, and related metabolic disorders [37].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are extracellular microvesicles (30 to 150 nm in diameter) derived from various cells, transferring different proteins, non-coding RNA and coding RNA, which have been looked as diseases biomarkers or cellcell communication factors [31,32]. Increasing studies have unveiled that exosomes derived from the insulinresistant adipocyte were implicated in the skeletal muscle insulin resistance, obesity-related liver disease, atherosclerosis, and lung cancer [33][34][35][36]. Given the broad spectrum of the discoveries of the function of these exosomes, it is not surprising that exosomes derived from insulin-resistant adipocytes, functioned as independent metabolic units, which might provide a promising therapeutic target on the insulin resistance, diabetes, and related metabolic disorders [37].…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that addition of PA promotes hypertrophy in adipocytes and that miR27a may be derived from hypertrophic adipocytes in the obese state 12 . To determine the direct effect of adipocyte derived miR27a on the development of macrophage characteristics in 3T3-L1 preadipocyte cells, 3T3-L1 preadipocytes were incubated for 48 h with conditional medium prepared from differentiated 3T3-L1 adipocytes incubated under various conditions (con, CM1, CM2 and CM3) and phagocytosis and cell migration were subsequently examined.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that miR27a is mainly secreted by adipocytes under obese conditions and is capable of regulating insulin resistance in skeletal muscle 12 . Whether local adipose tissue secreted miR27a promotes macrophage-like development of adipose precursor cells was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle consumes nearly 80% of glucose [10], and liver regulates glycogen storage, glucose uptake and output [11], indicating skeletal muscle and liver play an important role in glucose homeostasis. Glucose homeostasis is disrupted when the insulin signal pathway is suppressed in liver and muscle [12,13]. In the present study, the insulin signaling pathway in the liver and muscle of the HE offspring was examined to explore the molecular mechanism underlying their impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 98%